Outsourcing Workers Legal Protection Under The Post Validation Of Job Creation Law - Indah Kesuma; Aloysious Uwiyono (Unram Law Review, 2022)
The enactment of job creation law considers as the government effort to develop the ecosystems of competitiveness and investment in Indonesia. Even though there are many rejections, the government are optimistic that this provision could provide significant improvement for various sectors such as the sector on manpower. The research aim is to understand the concept changes and outsourcing requirements based on the job creation Act. The method of this research using legal doctrine or normative juridical method by conducting references through secondary data studies. In Legal research, secondary data includes primary legal materials, secondary legal materials, and tertiary legal materials. The research result illustrates that the protection of workers/labor, their wages and welfare, the working conditions also if disputes arise will be carried out by virtue of the regulations and are the responsibility of outsourcing company. The obstacles may emerge such as the absence of obligations under the outsourcing contract. Therefore, the legal certainty is not existed to protect the workers, since the legal protection for workers are according to the agreement.